Annotated bird sighting list for winter 1980 and 1981 compiled by Thomas H. Kent - Kent, Thomas H. (Thomas Hugh), 1934-et al (1981)
An annotated list of birds sighted by Thomas H. Kent and others, mostly in areas around eastern Iowa. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of winter 1980-1981. Epson - sheet feed/flatbed